Identifying potential areas for an expanding wolf population in Sweden. (April 2018) - Eriksson, Therese; Dalerum, Fredrik
Abstract: Large carnivores have historically been decreasing worldwide, often as a result of human-carnivore conflicts. However, large carnivores are recovering throughout Europe, and European management scenarios can provide important insights into broad issues related to human-large carnivore existence. After becoming almost extinct in Sweden during the mid-19th century the Swedish grey wolf ( Canis lupus ) population has now recovered. Current national wolf management aims to promote distribution shifts from the current areas in central Sweden, potentially also into a previously exempt reindeer husbandry area. Prior wolf re-introductions have highlighted the necessity of pro-active management for colonization success. Identification of likely range expansion areas could therefore be paramount for a successful Swedish wolf management. We characterized the demographic and spatial progression of Swedish wolves during 2001–2015 and used a MaxEnt approach to species distribution models to identify potential range expansion areas. The Swedish wolf population had expanded from 10 to almost 60 reproductions or territorial pairs, and increased in both range size and density. Our distribution models suggested that Swedish wolf management may face trade-offs between costs of hosting wolves in densely populated areas in southern Sweden with cattle and sheep and the costs of allowing wolves to expand into reindeer husbandry areas with associated cultural and economic consequences. Spatially explicit data on the economic, social and cultural factors associated with wolf conflict and acceptance may be paramount for developing optimal management strategies in the face of such a trade-off. Graphical abstract: Unlabelled Image Highlights: The Swedish wolf population has shown a strong demographic expansion 2001–2015. A management policy has restricted the geographic distribution of Swedish wolves. Suitable range expansion areas were primarily found in northern or southern Sweden. Swedish wolf management will face trade-offs associated with future distribution. Policy can impact carnivore distributions more than environmental characteristics.